A aplicação do princípio da subsidiariedade como forma de alcançar a universalidade na seguridade social por meio do subsistema de assistência social - Teles, Katia Cristine Oliveira (2017)
The aim of this thesis is to analyze the application of the principle of subsidiarity as a way of achieving universality in social security through the social assistance subsystem. Part of the constitutional prescription (article 201) that social security is due to the worker, but that there is a part of the Brazilian population that does not work or is in precarious working conditions, and that demands social protection in view of their vulnerability situation , Which leads to marginalization. Therefore, in order to understand how this protection is promoted, it is necessary to approach the evolution of this social coverage, in order to arrive at the current protective model in Brazil (Social Security System), where social assistance is inserted and has Relevance in order to act in the most vulnerable social centers, with a view to reducing and minimizing social imbalance. In order to do so, it seeks to analyze the economic benefits of social assistance related to direct income transfer programs, in order to clarify its main aspects and demonstrate the progress achieved from these benefits. In addition, in relation to the benefit of continuous benefit, it is worth noting that it deserves discussion of its value, since it competes with the floor of the social security. Regarding the methodological aspects, researches were carried out on official databases, as well as bibliographical and jurisprudential researches with the purpose of obtaining theoretical and empirical results of the reality of social security in Brazil, especially in relation to the accomplishment of social assistance in the search for universalization.